Freud, Lacan and Erotic Desire in Education - Stebbins, Anne (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
This article provides an analysis of Freudian and Lacanian notions of transference and relates the unconscious displacement of emotion to student-teacher relationships. It considers learning as a highly emotional experience and imagines chaotic and unruly desires as encouraging risky and pleasurable learning in feminist classrooms.